2013
DOI: 10.4236/jep.2013.410135
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grazing Intensity on Soil Properties and Shaping Herbaceous Plant Communities in Semi-Arid Dambo Wetlands of Zimbabwe

Abstract: Key issues of concern regarding the environmental impacts of livestock on grazing land are their effects on soil, water quality, and biodiversity. This study was carried out to determine how grazing intensity influences soil physical and chemical properties and occurrence of herbaceous plant species in dambo wetlands. Three categories of grazing intensity were selected from communal, small scale commercial and large scale commercial land. Dambos from the large scale commercial land functioned as the control. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Nevertheless, cattle trampling is reported by 9.8% household heads and 26.7% teenagers to be responsible for desiccation in unprotected wetland sections. The effect of cattle trampling on wetlands was also well studied (Sibanda, 2005;Dahwa et al, 2013;Morris and Reich, 2013).…”
Section: 32mentioning
confidence: 99%
“…Nevertheless, cattle trampling is reported by 9.8% household heads and 26.7% teenagers to be responsible for desiccation in unprotected wetland sections. The effect of cattle trampling on wetlands was also well studied (Sibanda, 2005;Dahwa et al, 2013;Morris and Reich, 2013).…”
Section: 32mentioning
confidence: 99%
“…Several studies have demonstrated that grazing intensity is one of the main drivers of wetland ecosystem dynamics (Marty, 2005; Jones et al, 2011; Dahwa et al, 2013). For instance, high grazing intensity is strongly correlated with high plant mortality and low recruitment rates, leading to changes in community structure and loss of species diversity (Milchunas et al, 1988;Gordon et al, 2004;Mysterud, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive grazing can result in the ecological disturbance of vulnerable grassland and wetland ecosystems leading to biodiversity loss and biological invasions (Milchunas and Lauenroth, 1993;Perevolotsky and Seligman, 1998;Marty, 2005;Dahwa et al, 2013). Thus the response of local and regional biodiversity to grazing may be positive or negative depending upon its intensity and frequency and the species specific responses of the constituent vegetative and herbivore taxa (Freilich et al, 2003;Maestas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, variations in the availability of nutrients and water content in the soil on a small scale, form microhabitats that harbor herbaceous populations more numerous (Haskell, Flaspohler, Webster, & Meyer, 2010;Dahwa et al, 2013). Although we have not quantified the soil properties in this study, it is possible that they can mitigate the effect of temporal variation in precipitation and contribute to the maintenance of some herbaceous populations of the caatinga.…”
Section: Discussionmentioning
confidence: 98%